Visions of freedom : Havana, Washington, Pretoria and the struggle for southern Africa, 1976-1991 - Gleijeses, Piero (New Cold War history., 2013)
During the final fifteen years of the Cold War, southern Africa underwent a period of upheaval, with dramatic twists and turns in relations between the superpowers. Americans, Cubans, Soviets, and Africans fought over the future of Angola, where tens of thousands of Cuban soldiers were stationed, and over the decolonization of Namibia, Africa's last colony. Beyond lay the great prize: South Africa. The author uses archival sources, particularly from the United States, South Africa, and the closed Cuban archives, to provide an international history of this important theater of the late Cold War.